2018
DOI: 10.1111/bph.14200
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein‐27 and sex‐selective regulation of muscarinic and proteinase‐activated receptor 2‐mediated vasodilatation: differential sensitivity to endothelial NOS inhibition

Abstract: HSPB1 can regulate intact vascular endothelial function to affect NO-mediated vascular relaxation, especially in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Consistent with a role for HSP27 in barrier recovery, we showed that treatment of female mice with J2 enhanced vascular leakage induced by the activation of PAR1 but failed to affect VEGF-induced vascular leakage. Note that a previous study using HSPB1 -null mice ( HSPB1 encodes HSP27) observed sex-selective sensitivity to endothelial nitric oxide synthase inhibition, with female mice exhibiting greater sensitivity than male mice ( 40 ). These findings raise the possibility that modulation of vascular leakage observed with J2 may exhibit sex-selective sensitivity, but this has not been tested.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with a role for HSP27 in barrier recovery, we showed that treatment of female mice with J2 enhanced vascular leakage induced by the activation of PAR1 but failed to affect VEGF-induced vascular leakage. Note that a previous study using HSPB1 -null mice ( HSPB1 encodes HSP27) observed sex-selective sensitivity to endothelial nitric oxide synthase inhibition, with female mice exhibiting greater sensitivity than male mice ( 40 ). These findings raise the possibility that modulation of vascular leakage observed with J2 may exhibit sex-selective sensitivity, but this has not been tested.…”
Section: Discussionmentioning
confidence: 91%
“…Wire-myograph vascular bioassays. Isometric tension studies using a wire myograph were performed, as described previously (5,8,13). In brief, descending aorta tissue was cut into 2-mm-long rings as outlined above and mounted in the myograph.…”
Section: Methodsmentioning
confidence: 99%
“…However, further research is needed to translate hypoxic exposure interventions to the clinical setting. In a study of HSP27-deficient and overexpressing mice, Venu et al (105) found that HSP27 can affect mRNA levels of endothelial nitric oxide synthase (eNOS) and soluble guanylate cyclase, as well as the proportion of vasodilation that is sensitive to the action of L-N G -nitro arginine methyl ester (L-NAME), thereby influencing nitric oxide-mediated vascular relaxation by regulating intact vascular endothelial function.…”
Section: The Therapeutic Intervention Of Hsp27 41 Atherosclerosismentioning
confidence: 99%